Evaluation of Preference of Root Canal Irrigants By Students for Pulpectomy - MENON, ANIRUDDH; MATHEW, MEBIN GEORGE; VADIVEL, JAYANTH KUMAR (The journal of contemporary issues in business and government, 2021)
The present study was undertaken to evaluate the preference of root canal irrigants for pulpectomy of primary teeth in at Saveetha Dental college. Retrospective data of 2438 patients was obtained and segregated who visited between June 2019 to April 2020. Once the data was obtained it was statistically analyzed using SPSS by IBM version 20.The most commonly used out of the irrigants preferred in the present study the was saline (59%) followed by saline with a combination of EDTA (32.5%), followed by EDTA alone (8.4%) and the least used irrigant was a combination of saline and sodium hypochlorite (0.1%). Saline was the most preferred irrigant in both the undergraduate and postgraduate clinics.Within the limits of the present study it was observed that the most common type of irrigant that was used is saline (59.03%). Further studies are to be done to formulate a clear and distinct clinical practice guideline for pulpectomy procedure.Further awareness programmes that should be conducted to bring out better clinical outcomes and help the society holistically.